Lectures on economic and financial sector reforms in India - Reddy, Y. (New Delhi, 2002)
The essays in this volume are based on lectures delivered by Y.V. Reddy in various parts of the world. They discuss the complex but under documented structural micro-aspects of economic reforms in India, examining the process from conceptualization of policy to its development, refinement and implementation. The book explores dilemmas and issues faced by policy. makers in meeting the evolving uncertainties.
Keywords: Financial reforms-India